Conservation Laws and Exact Solutions for a Reaction-Diffusion Equation with a Variable Coefficient - Zhijie Cao; Yiping Lin (Abstract and Applied Analysis)
In this paper a variable-coefficient reaction-diffusion equation is studied. We classify the equation into three kinds by different restraints imposed on the variable coefficient b(x) in the process of solving the determining equations of Lie groups. Then, for each kind, the conservation laws corresponding to the symmetries obtained are considered. Finally, some exact solutions are constructed.